2016
DOI: 10.1007/s10695-016-0210-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of starvation and re-feeding on growth and swimming performance of juvenile black carp (Mylopharyngodon piceus)

Abstract: We investigated the effects of starvation and re-feeding on growth and swimming performance and their relationship in juvenile black carp (Mylopharyngodon piceus). We measured the specific growth rate (SGR), resting metabolic rate (RMR) and constant acceleration test speed (U CAT, the maximum swimming speed at exhaustion by constant acceleration test with 0.1667 cm s(-2) rate) in a treatment group (21 days of starvation then 21 days of re-feeding) and control group (routine feeding) (n = 20). Starvation result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
1
8
2
1
Order By: Relevance
“…No significant difference in body weights and biomass was found bet-ween one-week deprived group and the group without feed deprivation. Similar effects of feed deprivation on growth and body composition were also reported in previous studies (Oh et al, 2007;Morshedi et al, 2013;Yengkokpam et al, 2014;Pang et al, 2016). The present study showed that tilapia were unable to compensate weight losses during two weeks of feed deprivation period, which resulted in significantly lower body weight and biomass compared to the other groups at the end of the experiment.…”
Section: Resultssupporting
confidence: 89%
“…No significant difference in body weights and biomass was found bet-ween one-week deprived group and the group without feed deprivation. Similar effects of feed deprivation on growth and body composition were also reported in previous studies (Oh et al, 2007;Morshedi et al, 2013;Yengkokpam et al, 2014;Pang et al, 2016). The present study showed that tilapia were unable to compensate weight losses during two weeks of feed deprivation period, which resulted in significantly lower body weight and biomass compared to the other groups at the end of the experiment.…”
Section: Resultssupporting
confidence: 89%
“…Similar downregulation of SMR has been noted in other species, possibly as an adaptation to reduce energy expenditure during food deprivation, but generally after a longer time period without food ( O'Connor et al, 2000 ; Yang and Somero, 1993 ). For example, black carp ( Mylopharyngodon piceus ) only show a 30% decrease in SMR after 21 days of fasting at 25°C, whereas, in the present study, southern catfish showed a 60% decrease in SMR after 2 weeks ( Pang et al, 2016 ). In the current study, it is possible that changes in spontaneous activity within the respirometers may have contributed to the observed differences in estimated SMR among feeding periods.…”
Section: Discussioncontrasting
confidence: 71%
“…During refeeding, fish showed an extreme increase in body size, with their average mass increasing by more than 3-fold after 15 days refeeding, a rate much faster than most fish species under comparable conditions ( Pang et al, 2016 ). In general, the southern catfish is a very fast-growing species, with more than 60% of ingested energy being channeled to growth and potentially reaching 3–4 kg in their first year when food is abundant [with maturation occurring at about 5–7 years ( Xie and Sun, 1987 )].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic rates are typically thought to have important impacts on fitness, and interindividual variation in metabolic rate is thought to be repeatable over time (Norin and Malte, 2011). Somatic growth is one of the most fundamental biological processes required for survival and thus has important fitness consequences, and growth rate is frequently used as an indicator of the capacity to acquire food resources (Arnott et al, 2006;Stephen et al, 2006;Pang et al, 2016a). It has long been suggested that maintenance metabolism (i.e.…”
Section: Introductionmentioning
confidence: 99%